Information about Policy Debates - Kelly, Erin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Central Goals of Assignment: 1) Convince the class that, given limited resources (including money, advocacy efforts, and the public’s attention), your proposed policy change is the most important and most effective way to help working families in the U.S. 2) Teach the class something new about the need for a change in policy or practice, the current policy / situation, and the main proposals for change. 3) Take the opportunity to synthesize class readings and materials as you prepare for the debate. 4) Learn from and with each other.